Israeli-Palestinian conflict: towards a major logistical and environmental crisis? - Paché, Gilles (Technium Social Sciences Journal, 2024)
Since October 2023, the Middle East has once again experienced a dramatic episode in its history, with an Israeli-Palestinian conflict following a bloody terrorist attack on Israeli territory by 3,000 Hamas assailants. At the end of 2023, the Gaza Strip, at the heart of violent fighting, was experiencing a catastrophic situation for its population, leading many NGOs to speak of a major humanitarian crisis. While this is an essential issue, it should not conceal the possibility of a logistical and environmental crisis. This research note highlights the potential impacts of the Israeli-Palestinian conflict, pointing out that they are most often common to all military conflicts. However, a few weeks after the October 2023 terrorist attack, the logistical crisis in global supply chains has been averted, while the environmental crisis is inevitable for the Gaza Strip.